1993
DOI: 10.1021/j100143a012
|View full text |Cite
|
Sign up to set email alerts
|

An isotopic and EPR probe into hyperconjugative and induction effects in p-xylene

Abstract: EPR studies show that the anion radicals of a,a,a-d3-p-xylene and a,a'-ds-p-xylene (CD3-CaHd-CD3'-) exhibit hyperfine coupling constants for the ring protons that are 12 and 23 m G larger than those of the p-xylene anion radical itself. This has been attributed to a further lifting of the degeneracy of the antibonding molecular orbitals due to the replacement of the protons with deuteriums to an extent of 29 J/mol per deuterium. These results seem to support the conclusion that both inductive and hyperconjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Finally, the hyperfine interaction with the 17 O isotope ( I = 5 / 2 ) provides direct information about the spin density at the tyrosine radical phenol oxygen. Note that there is no 13 C- or 17 O-isotope effect on the spin-density distribution in the π-radical. , The expected small changes of the α-proton hfi upon deuteration of the β-methylene hydrogens were ignored …”
Section: Introductionmentioning
confidence: 99%
“…Finally, the hyperfine interaction with the 17 O isotope ( I = 5 / 2 ) provides direct information about the spin density at the tyrosine radical phenol oxygen. Note that there is no 13 C- or 17 O-isotope effect on the spin-density distribution in the π-radical. , The expected small changes of the α-proton hfi upon deuteration of the β-methylene hydrogens were ignored …”
Section: Introductionmentioning
confidence: 99%
“…Although their results, especially those dealing with 15 N/ 14 N and 13 C/ 12 C isotope effects, have been questioned from theoretical and experimental standpoints, , Stevenson and co-workers argued later that the EIE is strongly dependent on the charge and spin density in the area of isotope substitution, which is, in turn, dependent on the specific anion radical/counterion and anion radical/solvent interactions that make the statistical mechanical calculation hard to account for. The H/D isotope effects that Stevenson and co-workers initially observed via electron spin resonance (ESR) measurements 1 have been confirmed by independent cyclic voltammetric data , and theoretical calculations. , …”
Section: Introductionmentioning
confidence: 76%
“…Stevenson and co-workers , have published a series of papers since 1986 dealing with the equilibrium isotope effect (EIE) on electron-transfer processes between several radical anions and their heavy-isotope-substituted aromatic molecule precursors. They found that the equilibrium constants for the electron exchange (eq 1) deviated significantly from unity and suggested that these EIE's may serve as a basis for an efficient isotope separation: where *A represents a heavy isotope ( 2 H, 13 C, 15 N, 17 O, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…6,12 The substitution of hydrogen by weakly perturbing alkyl groups, like the methyl group in toluene and xylene anions, removes the 2-fold orbital degeneracy of the ground state of benzene radical cations/anions artificially. 13,14 The radical cations of toluene and xylene in silica gel and halocarbon matrices have been reported previously. [15][16][17] The hyperfine coupling constants determined in these investigations were different and a detailed assignment of the spectra is still lacking.…”
Section: Introductionmentioning
confidence: 89%
“…In contrast to many radical cations of aromatic hydrocarbons, the radical cations benzene, toluene, and xylenes are difficult to stabilize and study in solutions. However, these radical cations can be prepared in glassy rigid matrices of certain halocarbons or on surfaces of zeolite or silica gel. The benzene cation is of fundamental interest because it possesses an orbitally degenerated ground state e 1g ( D 6 h ) and is subjected to a Jahn−Teller distortion at low temperature. , The substitution of hydrogen by weakly perturbing alkyl groups, like the methyl group in toluene and xylene anions, removes the 2-fold orbital degeneracy of the ground state of benzene radical cations/anions artificially. , The radical cations of toluene and xylene in silica gel and halocarbon matrices have been reported previously. The hyperfine coupling constants determined in these investigations were different and a detailed assignment of the spectra is still lacking. Komatsu et al studied the radical cations of toluene and partly deuterated toluene (toluene α - d 3 ) on silica gel and Vycor glass and gave unambiguous evidence for the formation of toluene radical cation.…”
Section: Introductionmentioning
confidence: 99%